Three Studies in Roman Public Bathing: Origins, Growth and Social Aspects - Fagan, Garrett G. (My University, 1993)
For ancient Romans, a trip to the public baths was one of the central events of daily life. The copious physical remains of these buildings have been studied in detail by archaeologists and art historians, but many facets of their history and functioning remain unclear or disputed. This dissertation attempts to fill some of the gaps in our knowledge of this core institution in Roman community life. Three aspects are selected for close study: the origins of the baths; the growth of their popularity; and some social aspects of their daily operation. To date these questions have been respectively not satisfactorily addressed, glossed over, or treated only in the most general terms. The approach taken in the first section, unlike previous studies, is to emphasize the human side of the baths' origins: what drove the Romans (or, more precisely, the Carnpanians) to create their distinctive bathing facilities? Previous theories, mostly based on archaeological evidence, are examined in detail and found to be unsatisfactory. The admittedly sparse literary and epigraphic evidence is subjected to close critical scrutiny. All three types of primary source are then combined to form a new hypothesis which better fits all the evidence than the often fanciful proposals which still carry currency among Roman balneologists. Section two is concerned with tracing and explaining the growth in the baths' popularity in the 1st centuries BC and AD. Again, archaeological and written evidence is combined to determine the main periods of growth. In searching for an explanation for the phenomenon, it is suggested that the medical teachings of the famous doctor Asclepiades of Bithynia may have played an important, if not precisely quantifiable, role in the spread of the bathing habit in the city. The main basis for section three is the tabulated epigraphic evidence, a largely untapped source for the study of the baths. Using these data (as well as material drawn from other sources) an investigation is conducted into the identities, motives, and social statuses of bathbuilders and rnaintainers. In addition, an attempt is made to reconstruct from available evidence the social environment to be found at the baths. In the course of the inquiry, some consequences for broader topics in Roman social history are highlighted.
Keywords: Roman Public Bathing; Origins